THE PERSPECTIVE OF GAS DISTRIBUTION FROM THE RUSSIAN FEDERATION ON THE WORLD MARKET - VESELINOVIĆ, Milan; STANOJEVIĆ, Jelena; GASHI, Damir (Journal of process management and new technologies, 2025)
In recent years, the world has witnessed a concerning rise in unrest, causing considerable disruptions across multiple sectors. The Russian Federation's incursion into Ukraine has generated widespread consequences, affecting global production, trade, energy supplies, and inflation. European Union member states have been notably impacted, encountering difficulties in securing oil and gas supplies. As Germany and other EU countries contend with these challenges, particularly those arising from sanctions on Russia, the crisis holds the potential to pave the way for one of the most significant energy alliances in modern history. This development could strengthen and expand economic ties between Russia, a major global exporter of oil and gas, and China, one of the world's largest energy consumers. As these connections grow, a more pronounced political divide between the East and West is anticipated, underscored by extensive and strategic investments in infrastructure for the transportation, storage, and distribution of gas